2016
DOI: 10.1177/1934578x1601101015
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic Fungal Exopolysaccharides Produced by Fungi Involved in Grapevine Trunk Diseases

Abstract: This paper reports the isolation and chemical and biological characterization of exopolysaccharides produced by phytopathogenic fungi belonging to different genera and inducing various diseases on grapevine. Their role in the phytopathogenic processes is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 20 publications
(36 reference statements)
1
14
0
Order By: Relevance
“…The ethanolic phases were recovered and the precipitates resuspended and again precipitated as above. The polysaccharide content of the precipitates was measured following a recently described procedure . The standards of jasmonic acid ( 6 ), cis -(3 R ,4 R )- and trans -(3 R ,4 S )-(−)-4-hydroxymelleins ( 2 and 3 ), scytalone, and isosclerone were compared by TLC analysis with the residues obtained from both ethanolic phases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ethanolic phases were recovered and the precipitates resuspended and again precipitated as above. The polysaccharide content of the precipitates was measured following a recently described procedure . The standards of jasmonic acid ( 6 ), cis -(3 R ,4 R )- and trans -(3 R ,4 S )-(−)-4-hydroxymelleins ( 2 and 3 ), scytalone, and isosclerone were compared by TLC analysis with the residues obtained from both ethanolic phases.…”
Section: Methodsmentioning
confidence: 99%
“…The polysaccharide content of the precipitates was measured following a recently described procedure. 31 The standards of jasmonic acid (6), cis-(3R,4R)-and trans-(3R,4S)-(−)-4-hydroxymelleins (2 and 3), scytalone, and isosclerone were compared by TLC analysis with the residues obtained from both ethanolic phases. The samples containing jasmonic acid were also analyzed by LC/MS.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Those obtained by N. parvum were characterized as a mannan with a backbone consisting of (1→6)-linked mannopyranose units almost all branched at the 2 position, whereby the arms are made up of 2- and/or 3-linked units. When adsorbed by detached grapevine leaves, these EPS induced likewise reddening and withering depending on the tested concentration and time from absorption [ 19 ]. The EPSs produced by P. chlamydospora were also used to develop a flow cytometry method that unequivocally identifies some of the toxic metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…parvum can produce a plethora of low-molecular-weight compounds that showed toxic effects on grapevine and tomato leaves and grapevine calli. , Recently, exopolysaccharides have been obtained from the culture filtrates of an isolate of N. parvum and tested on grapevine leaves, showing different degrees of toxicity . However, more in-depth investigations are required to understand the effective role of these extracellular compounds in the disease development and symptom expression.…”
mentioning
confidence: 99%
“…5,10 Recently, exopolysaccharides have been obtained from the culture filtrates of an isolate of N. parvum and tested on grapevine leaves, showing different degrees of toxicity. 11 However, more in-depth investigations are required to understand the effective role of these extracellular compounds in the disease development and symptom expression. Investigations by Beńard-Gellon et al 7 showed that N. parvum produced aggressive extracellular proteins, causing necrosis and inducing an upregulation of grapevine defense genes.…”
mentioning
confidence: 99%